An Impact Analysis Of Work Experience, Job Satisfaction, And Engagement On The Performance Of Gen Z Civil Servants: A Quantitative Study At The Surabaya Education Department - Setia, Shinta; Bella Juliandita, Elivia (Benefit: Jurnal Manajemen dan Bisnis, 2025)
As technology and digitalization evolve at a rapid pace, Generation Z is starting to dominate the workforce. Many industries, notably the State Civil Apparatus sector (Aparatur Sipil Negara/ASN), are exhibiting this generational change. Creating a great work experience poses new problems since Gen Z differs from earlier generations in many ways. This study intends to investigate how Gen Z State Civil Apparatus performance in the Surabaya Education Office is impacted by employee experience, job satisfaction, and engagement. A survey method was used to conduct a quantitative study, and 233 Gen Z employees were given questionnaires to complete in order to gather data.. The SmartPLS program was used to analyze the data using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that job happiness, employee engagement, and employee experience all significantly and favorably impact employee performance. These findings imply that improving these three elements may help Gen Z civil servants perform better.